A new species of the genus Tagasta Bolivar, 1905 (Orthoptera: Pyrgomorphidae) from India - Gupta, Sunil Kumar; Chandra, Kailash; Yin, Hai-Xiang (Zootaxa, 2020)
Tagasta mizoramensis sp. nov. is described from Dampa Wildlife Sanctuary, Mizoram, India. The type specimens are deposited in the Central Entomological Laboratory, Zoological survey of India.